The Going‐Public Decision and the Development of Financial Markets - Subrahmanyam, Avanidhar; Titman, Sheridan (Journal of Finance, 1999)
This paper explores the linkages between stock price efficiency, the choice between private and public financing, and the development of capital markets in emerging economies. Generally, the advantage of public financing is high if costly information is diverse and cheap to acquire, and if investors receive valuable information without cost. The value of public firms generally depends on public market size, which implies that there can be a positive externality associated with going public, so that an inferior equilibrium can exist where too few firms go public. The model is consistent with empirical observations on financial market development.